2021
DOI: 10.1016/j.jcmgh.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Acute Intestinal Inflammation Depletes/Recruits Histamine-Expressing Myeloid Cells From the Bone Marrow Leading to Exhaustion of MB-HSCs

Abstract: Background & Aims Histidine decarboxylase (HDC), the histamine-synthesizing enzyme, is expressed in a subset of myeloid cells but also marks quiescent myeloid-biased hematopoietic stem cells (MB-HSCs) that are activated upon myeloid demand injury. However, the role of MB-HSCs in dextran sulfate sodium (DSS)-induced acute colitis has not been addressed. Methods We investigated HDC+ MB-HSCs and myeloid cells by flow cytometry in acute intestinal inflammation by treating H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The copyright holder for this preprint this version posted March 1, 2023. ; https://doi.org/10.1101/2023.02.28.530500 doi: bioRxiv preprint homeostasis but become more abundant during disease states. These cells are rapidly mobilized in response to inflammatory conditions to fight infection and promote tissue repair, but such mobilization promotes activation of HSCs, which can eventually lead to their exhaustion if such activation is sustained (Fu et al, 2021). Although it was known these cells infiltrate damaged tissues to promote regeneration, their functions therein have been understudied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted March 1, 2023. ; https://doi.org/10.1101/2023.02.28.530500 doi: bioRxiv preprint homeostasis but become more abundant during disease states. These cells are rapidly mobilized in response to inflammatory conditions to fight infection and promote tissue repair, but such mobilization promotes activation of HSCs, which can eventually lead to their exhaustion if such activation is sustained (Fu et al, 2021). Although it was known these cells infiltrate damaged tissues to promote regeneration, their functions therein have been understudied.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Hdc + IMCs are mobilized from the bone marrow to the colon during DSS-induced colitis (Fu et al, 2021). To test if Hdc + IMCs are involved in intestinal regeneration, we employed a model of 12 Gy whole-body irradiation (WB-IR), which induces acute damage to the intestinal epithelial stem and progenitor zone cells (Booth et al, 2012).…”
Section: Hdc+ Imcs Are Recruited To the Damaged Intestine Following I...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, gut microbes can shape bone metabolism by influencing immune responses and altering relative OCL and OB activity levels via the production of specific metabolites. [10][11][12] Dietary calcium is absorbed into the blood via calcium channels within the small intestinal epithelium and through active transport mechanisms, whereupon it is passively transported throughout the entire gastrointestinal tract. IBD can result in alterations in the composition of the gut microbiota, leading to changes in the secretion of particular shortchain fatty acids as well as changes in the lumenal pH within the intestines, thereby impairing calcium absorption and resulting in dysregulated bone metabolism that can further progress to cause osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cellular and Molecular Gastroenterology and Hepatology, Fu et al 6 from the Wang laboratory sought to explore the role of HDC-expressing myeloid cells and MB-HSCs in the setting of acute colitis by using the dextran sulfate sodium (DSS)-induced intestinal injury model of inflammatory bowel disease. Although the mechanism by which DSS induces intestinal inflammation is not entirely clear, it is likely the result of epithelial damage of the lining of the large intestine that allows infiltration of proinflammatory luminal contents such as bacteria and their products into underlying mucosa and subsequent activation of the innate immune system.…”
mentioning
confidence: 99%